ANALISIS FAKTOR RISIKO TERJADINYA HIPERTENSI PADA REMAJA USIA 15-18 TAHUN DI WILAYAH KEPANJEN - Frastiqa Fahrany (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Hypertension is a complex health problem with many influential factors. Hypertension which was previously a disease that mostly affects adults, is now increasingly widespread in children and adolescents, especially at the age of less than 19 years. The purpose of this study is to identify risk factors that play a role in the occurrence of hypertension in adolescents aged 15-18 years. The study design used correlational research with cross sectional approach. Samples were taken by means of purposive sampling of Vocational High Schools in Kepanjen Area totaling 176 people. In this study, data taken included age, sex, family history, body mass index (BMI), abdominal circumference, physical activity, and smoking behavior. This study uses a bivariate analysis using the chi square test and the fisher test and subsequently a multivariate test using logistic regression. The logistic regression test results obtained significance of 0.024 physical activity and smoking behavior of 0.008. This shows that physical activity and smoking is the most influence the occurrence of hypertension in adolescents aged 15-18 years. The conclusion from this study that the highest effect in hypertension in adolescents aged 15-18 years are physical activity and smoki8ng behavior. Suggestions based on the results of this study are expected to be carried out further studies related to other factors that influence and are more specified in systolic and diastolic blood pressure.